Análise das principais causas de troca de esquemas anti-retrovirais no tratamento de Aids em crianças atendidas no ambulatório do Hospital Infantil Nossa Senhora da Glória - Macedo, Cristina Ribeiro (2006)
The study was developed in the Infectious Deseases Ambulatory of the Hospital Infantil Nossa Senhora da Glória (HINSG), Vitória (ES), Brazil. From the 230 children that were included, 98 were exposed to HIV virus so they were followed to asses their serum status and 116 children that where were on anti-rethroviral therapy. Several children were in an advanced stage of the infection and had already used differents schemes of treatment.This is a case-control study, with a control group of 49 children without changes in their therapeutical scheme since January 2000 till December 2005 and the case group of 62 children that changed at least once their drugs on the same period. The objective was to identify the reasons for changing the therapeutical scheme of AIDS treatment in children with vertical contamination and how they match with treatment adhesion, throught two variables: failure of treatment and intolerance. Anamnesis data and a standard interview with open and shut questions to the caretakers were used and the results were analised with square chi test to weigh the association of variables using SPSS 8.0 for Windows. The main reasons for the treatment change were viral, inmunological or clinical worsening in 30 (48,4%); 29 (46,6%) and 22 patientes (35,5%), and in 30 (50%) cases the change occurred in less than a year of treatment which represents a strong indicative of lack of adhesion. We conclued that all kind of efforts must be made to obtain adhesion, because it can save the life of a child with AIDS.